2010
DOI: 10.1016/j.tips.2010.04.001
|View full text |Cite
|
Sign up to set email alerts
|

Are formyl peptide receptors novel targets for therapeutic intervention in ischaemia–reperfusion injury?

Abstract: Ischaemia-reperfusion (I/R) injury is a common feature of several diseases associated with high morbidity and mortality, such as stroke and myocardial infarction. The damaged tissue displays cardinal signs of inflammation and microvascular injury that, unless resolved, lead to long-term tissue damage with associated dysfunction. Current therapies are limited and are often associated with many side effects. Increasing evidence suggests that members of the formyl peptide receptor (FPR) family, in particular huma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
84
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(90 citation statements)
references
References 106 publications
6
84
0
Order By: Relevance
“…Considering the present model of CPIP induced by I/R, these founds are also in agreement with the idea that targeting ALX/FPR2 receptors in both types of cells can be useful to treat symptoms of diseases in which pathophysiology relies importantly on vascular disturbances Dufton & Perretti, 2010), specially those involving I/R-induced injuries (Gavins, 2010).…”
Section: Discussionsupporting
confidence: 91%
“…Considering the present model of CPIP induced by I/R, these founds are also in agreement with the idea that targeting ALX/FPR2 receptors in both types of cells can be useful to treat symptoms of diseases in which pathophysiology relies importantly on vascular disturbances Dufton & Perretti, 2010), specially those involving I/R-induced injuries (Gavins, 2010).…”
Section: Discussionsupporting
confidence: 91%
“…Furthermore, FPRs are documented to regulate innate inflammatory responses and mediate cell migration in response to a variety of chemotactic factors by facilitating the trafficking of phagocytes to the site of bacterial invasion (44). Given the finding that RERF interferes with the complex cross-talk involving uPAR, FPR, and integrins, it is reasonable to foresee that this peptide may be also used to develop new drugs for the treatment of diseases that are sustained by a chronic excess of cell migration such as inflammatory diseases.…”
Section: Discussionmentioning
confidence: 99%
“…For example, mouse FPRs have been reported to be candidate chemosensory receptors in the vomeronasal organ (Liberles et al, 2009). Likewise, several studies have suggested that FPR2 agonists exhibit protective effects in ischemia-reperfusion models (for review, see Gavins, 2010). Overall, the demonstrated role of FPRs in orchestrating acute-phase inflammation supports the development of FPR agonists as novel anti-inflammatory therapeutics (Dufton and Perretti, 2010).…”
mentioning
confidence: 98%
“…N-Formyl peptides activate cells through formyl peptide receptors (FPRs), which are G protein-coupled receptors (GPCRs) (for review, see Ye et al, 2009). The three human FPRs (FPR1, FPR2, and FPR3) are expressed on a variety of cell types, including neutrophils, macrophages, T lymphocytes, epithelial cells, hepatocytes, fibroblasts, astrocytes, and other cells that serve a variety of regulatory functions during the host defense response (for review, see Ye et al, 2009;Gavins, 2010). For example, FPR1 and FPR2 have been implicated in control of endogenous inflammatory processes and initiation of proinflammatory neutrophil responses to pathogenic bacteria (Kretschmer et al, 2010).…”
mentioning
confidence: 99%